Blood pressure variability — 15 years later - V. M. Gorbunov; E. V. Platonova (Рациональная фармакотерапия в кардиологии)
Blood pressure variability (BPV) has been studied for a long time, and recently important new information has been obtained about the prognostic value of BPV and the influence of antihypertensive therapy on it. There are three groups of VBP characteristics that are most important from a practical point of view: 24-hour BPV, BPV of average duration and visit-to-visit variability (VVV). VVV has attracted the attention of scientists in recent years. In a recent study in patients who participated in the ASCOT-BPLA cohort (mean follow-up 17.4 years) it was shown that 1) SBP VVV proved to be a strong predictor of cardiovascular complications (CVC), independent of mean BP (and possibly stronger than the latter) including in patients with well-controlled AH; 2) the CVC risk (including stroke and coronary events) remained significantly lower in the amlodipine treatment group. This finding seems particularly interesting in view of the fact that during such a long follow-up period many patients changed their treatment regimen; baseline values of office BP in both groups did not differ significantly. Thus, the independent prognostic value of VVV has received new convincing confirmation. Amlodipine may be the optimal drug for the treatment of patients with elevated BPV, but further studies are required to prove this point.